Clinical, imaging, and laboratory characteristics of patients with COVID-19 according to ICU admission requirement in Cali, Colombia - Carmen Ocampo; Mónica Morales; Martín Cañón-Muñoz; Christian Pallares-Gutierrez; Karen Daniela López; Adrián Fernández-Osorio (Revista de la Facultad de Medicina, 2022)
Introduction: At present, few studies conducted in Latin America have addressed the demographic, clinical, and laboratory characteristics of patients with COVID-19 and intensive care unit (ICU) admission requirement.